The influence of the Muhadhoroh Program on improving students' Arabic speaking skills at Darul Musthofa Islamic Boarding School, Bengkulu." - Abdullah Haryono; Akhirudin (Al-Jawhar : Journal of Arabic Language, 2023)
The aim of this research is to determine the impact of the lecture program on enhancing students' speaking skills at Dar Al-Mustafa Institute in Bengkulu. It also aims to identify the Arabic language difficulties encountered by students at Dar Al-Mustafa Silomah Institute in Bengkulu. The research methodology employed in this study is quantitative research with an ex post facto approach. The data for this research includes all secondary and high school students, totaling fifty students, except for five students. The findings of this research indicate that implementing the Muhadhoroh program has an effect on improving the speaking skills of students at Dar Al-Mustafa Islamic Boarding School in Bengkulu.